Different stages of chemical alteration on metabasaltic rocks in the subduction channel: Evidence from the Western Tianshan metamorphic belt, NW China. (1st September 2017) - Xiao, Yuanyuan; Niu, Yaoling; Wang, Kuo-Lung; Iizuka, Yoshiyuki; Lin, Jinyan; Wang, Dong; Tan, Yulong; Wang, Guodong
Graphical abstract: Highlights: Large-scale fluid flows have been found to interact with metabasaltic rocks in subduction channel. Metabasaltic rocks have undergone different stages of chemical alteration in an open system. The traditional models for the petrogenesis of IAB and OIB need to be re-considered. Abstract: To understand the geochemistry of subduction zone metamorphism, especially the large-scale mass transfer at forearc to subarc depths, we carried out a detailed study of a ∼1.5 m size metabasaltic block with well-preserved pillow structures from the Chinese Western Tianshan high- to ultrahigh-pressure metamorphic belt. This metabasaltic block is characterized by omphacite-rich interiors gradually surrounded by abundant channelized (veins) glaucophane-rich patches toward the rims. The glaucophane-rich rims share the same peak metamorphic conditions with omphacite-rich interiors, but have experienced stronger blueschist-facies overprinting during exhumation. Representative samples from the glaucophane-rich rims and omphacite-rich interiors yield a well-defined Rb-Sr isochron age of 307 ± 23 Ma, likely representing this overprinting event. Both glaucophane-rich rims and omphacite-rich interiors show elevated K-Rb-Cs-Ba-Pb-Sr contents relative to their protolith, reflecting a large-scale enrichment of these elements and formation of abundant phengite during subduction. Compared with the omphacite-rich interiors, the glaucophane-rich rims have gained rare earth elements (REEs, >25%), U-Th (∼75%), Pb-Sr (>100%) and some transition metals like Co and Ni (25–50%), but lost P (∼75%), Na (>25%), Li and Be (∼50%); K-Rb-Cs-Ba show only 10% loss. These chemical changes would be caused by serpentinite-derived fluids during the exhumation in the subduction channel. Therefore, there are two stages of fluid action in the subduction channel. As the formation of phengite stabilizes K-Rb-Cs-Ba at the first stage, the residual fluids released from the phengite-rich metabasaltic rocks would be depleted in these elements, which are unlikely to contribute to elevated contents of these elements in arc magmas if phengite remains stable at subarc depths. In addition, the decrease of U/Pb ratios as the preferred enrichment of Pb over U in the eclogitic rocks during the first stage chemical alteration may further lead to the lower radiogenic Pb isotope component of the deeply subducted ocean crust with time, which is inconsistent with the high radiogenic Pb isotope component of high µ (= 238 U/ 204 Pb) basalts.